Ocular Gnathostomiasis in Brazil: A Case Report - Chaves, Cláudia M. (Ocul Oncol Pathol, 2016)
Gnathostomiasis is a parasitic disease caused by nematode larvae ingestion of 15 known species of the genus Gnathostoma (one of the Gnathostomatidae family members). This parasite uses freshwater fish as a host and can infect - through the consumption of raw fish or their viscera - other animals such as dogs, cats, chickens, pigs, and humans. This parasitic disease, with humans acting as hosts, has been known since 1945 (India), and ocular complications have been known since 2004 (intravitreal; also described in India). Latin American countries, especially Mexico and Peru, have reported cases of the disease since 1970. The first dermatological case was reported in Brazil in 2009 (the individual had acquired the disease in Peru). This article describes the first reported ophthalmic case of the disease in Brazil and refers to a male patient, 30 years old, living in the municipality of Juruá, Amazonas State. The disease evolved within 30 days through a fistulized tumor in the inner corner of the lower eyelid. Following excision, the anatomical and histopathological examination revealed the presence of a different parasite species from other previously known genera.